Make an in-depth study into the ways and extents to which the maritime industry may contribute to achieve related UN global goals (SDGs) - Afandi, Lee Swaleha (Nanyang Technological University, 2021)
This report seeks to examine the ways and extents by which the maritime industry may contribute to achieving the United Nations (UN) Sustainable Development Goals (SDGs). The SDGs were released by the UN in 2015. The document titled “Transforming our World: the 2030 agenda for sustainable development’ included 17 SDGs with 169 targets. The agenda aims for all countries to tackle sustainable development issues by stimulating actions towards economic, environmental, and social sustainability. The maritime industry plays a crucial role in achieving these SDGs due to its large dominance in global trade and economy. Therefore, this report will analyze the current regulations and practices of the maritime industry. A literature review will be carried out. To fill in the gaps from the literature review, interviews of the industry’s stakeholders will be carried out. Feedbacks from the stakeholders will enable a better understanding of the level of motivation and different criteria considered when contributing to an SDG. After consolidating all the findings based on thorough research and interviews, critical analysis will be carried out. Last but not least, this research paper will provide and evaluate several recommendations that demonstrate the ways and extents in which relevant stakeholders in the maritime industry can contribute to achieving the 2030 Agenda for Sustainable Development.